Description and Evaluation of the Writing Instruction Practices of a Coursebook - Papadaki, Aggeliki; Karagianni, Eleni (Eximia, 2023)
The purpose of the particular paper is to describe and evaluate the current writing instruction practices concerning a specific group of learners according to certain criteria, present an original writing lesson plan accompanied by its relevant writing tasks and evaluate it and finally, assess the whole writing lesson after teaching it. In the first part, there is a description of the current teaching situation, with reference to learners’ profile, the curriculum, the coursebook and the writing instruction practices used. In the second part, there is a brief description and evaluation of the writing instruction practices/ activities of the coursebook. In the third part, the original writing lesson that was created based on the criteria mentioned in the previous part is described, while at the same time there is a justification upon the activity choices. Finally, there is an overall evaluation of the writing lesson taught in class.